Characterization of liquid film distribution and sub-flow regimes of annular flow in helically coiled tubes using ring island array sensor. (March 2023) - Liu, Shuai; Wang, Ke; Liu, Li; Zhang, Qi; Gu, Hanyang
Highlights: Ring island array sensor for liquid film thickness measurement is developed. Circumferential distribution of liquid film in helically coil tube is obtained. Sub-flow regime map of annular flow in helically coil tube is proposed. Prediction model of flow regime transition boundaries is established. Abstract: The distribution of liquid film thickness in helically coiled tubes (HCTs) directly affects the heat transfer performance of the annular flow region. However, due to the limitation of measurement technology, accurate measurement data of liquid film thickness in HCTs is very rare. In this paper, a non-invasive contact liquid film thickness sensor (ring island array sensor) is successfully developed to obtain the refined three-dimensional spatial-temporal distribution data of liquid film thickness in HCTs. According to the results, four typical liquid film flow regimes are defined based on the circumferential position of the thicker liquid film appearing in the tube wall, i.e., the bottom distribution (BD) dominated by liquid phase gravity force, the outside distribution (OD) dominated by liquid phase centrifugal force, the inside distribution (ID) dominated by gas centrifugal force and the inside-outside distribution (IOD) dominated by the secondary flow. These circumferential distributions of liquid film thickness are mainly affected by the HCT structure (e.g., coil diameter and coil pitch) and superficial gas-liquid velocities. Based on the modified Dean number De * and the modified Lockhart-Martinelli parameter X *, which consider the influence of HCT structures, fluid properties and operating parameters, a general sub-flow regime map of annular flow is proposed. The prediction models of transition boundaries of different liquid film flow regimes are also established and verified with present and available data in the literature.